2008
DOI: 10.1007/s11145-008-9135-9
|View full text |Cite
|
Sign up to set email alerts
|

The syllable frequency effect in visual recognition of French words: a study in skilled and beginning readers

Abstract: The present study addressed the issue of syllable activation during visual recognition of French words. In addition, it was investigated whether word orthographic information underlies syllable effects. To do so, words were selected according to the frequency of their first syllable (high versus low) and the frequency of the orthographic correspondence of this syllable (high versus low). For example, the high-frequency syllable /ã/ is frequently transcribed by the orthographic cluster an, but infrequently tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 40 publications
4
31
0
12
Order By: Relevance
“…This supports an orthographic locus of syllabic effects. The relevant syllable-like units processed within written polysyllabic words predominantly correspond to letter clusters rather than to phonological syllables (see Chetail & Mathey, 2009;Conrad et al, 2010; but see Conrad et al, 2007). Consistently, Stenneken, Conrad, Goldenberg, and Jacobs (2003) reported the case of a dyslexic adult with severe phonological impairments who exhibited a reliable syllable frequency effect.…”
Section: Regression Analysesmentioning
confidence: 84%
See 1 more Smart Citation
“…This supports an orthographic locus of syllabic effects. The relevant syllable-like units processed within written polysyllabic words predominantly correspond to letter clusters rather than to phonological syllables (see Chetail & Mathey, 2009;Conrad et al, 2010; but see Conrad et al, 2007). Consistently, Stenneken, Conrad, Goldenberg, and Jacobs (2003) reported the case of a dyslexic adult with severe phonological impairments who exhibited a reliable syllable frequency effect.…”
Section: Regression Analysesmentioning
confidence: 84%
“…An inhibitory effect was found, high syllable-frequency (HSF) words being processed more slowly than low syllable-frequency (LSF) words. Since that first report, the effect has been replicated in several languages: Spanish (Alvarez, Carreiras, & Taft, 2001;Conrad, Carreiras, & Jacobs, 2008;Conrad, Carreiras, Tamm, & Jacobs, 2009), French (Chetail & Mathey, 2009;Conrad, Grainger, & Jacobs, 2007; see also Mathey & Zagar, 2002) and German Hutzler, Conrad, & Jacobs, 2005;Stenneken, Conrad, & Jacobs, 2007). At a theoretical level, the effect has been accounted for in terms of competition among candidate words sharing the initial syllable (Carreiras et al, 1993).…”
Section: Introductionmentioning
confidence: 88%
“…In the lexical decision task, Carreiras et al (1993) observed that skilled readers in Spanish decided more slowly that words with a high-frequency first syllable were real words than words with a low-frequency first syllable. This inhibitory effect of syllable frequency has been widely replicated in follow-up studies in Spanish (e.g., Alvarez et al 2000Alvarez et al , 2001Conrad et al 2008;Perea and Carreiras 1998), French (e.g., Chetail and Mathey 2009b;Conrad et al 2007;Mathey and Zagar 2002;Mathey et al 2006) and German (e.g., Stenneken et al 2007;Conrad and Jacobs 2004). In reading aloud also, syllable frequency effects have been reported in the naming task, the effects being either facilitative (e.g., Macizo and Van Petten 2007, in English;Perea and Carreiras 1998, in Spanish) or inhibitory (e.g., Carreiras et al 1993, in Spanish;Conrad et al 2006, in German).…”
Section: The Syllabic Issue In Readingmentioning
confidence: 70%
“…When the effects of syllable frequency were separately examined according to the syllable features in French , data yielded an inhibitory effect of phonological syllabic neighbourhood (orthographic syllabic neighbourhood held constant) and no effect of orthographic syllabic neighbourhood (phonological syllabic neighbourhood held constant). Furthermore, when the phonological syllabic neighbourhood and the orthographic syllabic neighbourhood were jointly manipulated, the inhibitory effect of syllable frequency was obtained only for low-frequency orthographic syllables in adults, while the reverse pattern was found in fifth graders in French (Chetail and Mathey 2009b). These data suggest that the orthographic transcriptions of syllables is an important variable and that orthographic information carried by syllables should be taken into account when studying syllable effects, at least in French.…”
Section: Syllabic Effects and Orthographic Informationmentioning
confidence: 81%
See 1 more Smart Citation